Small steps towards bigger goals: A study of demography and outcome of paediatric cancers in a peripheral resource limited paediatric oncology centre - Bafna, Vibha S.; Bartakke, Sandeep P.; Sampagar, Abhilasha A.; Bafna, Tanvi A.; Patel, Putun K.; Aung, Nay; Gupta, Priya N.; Mahankar, Parag W. (International Journal of Contemporary Pediatrics, 2021)
Background: The aim of this study was to analyze the demography, clinical profile and outcome of pediatric cancer cases from a peripheral resource limited center. Methods: We retrospectively analysed demography, clinical details and outcomes of 227 cases of paediatric cancer up to nineteen years of age, from August 2009 to May 2019. Their status of treatment was categorised as completed, ongoing, abandoned and expired. We generated Kaplan-Meier curves (KM) and calculated three-year event free survival (EFS) and overall survival (OS). Results: Out of 227 children, 139 (61.2%) were boys and the rest were girls. Maximum number of children 108 (47.6%) were aged zero to four years. The socioeconomic status of 70 patients using the Kuppuswammy scale showed that 55 patients (78.57%) belonged to a lower socio-economic stratum. The commonest malignancy was leukaemia 119(52.4%) followed by solid tumours constituting 84 (37%) patients, of which 25 (11.01%) were renal tumours. Out of total 227 patients, 107 (47.13%) have completed treatment, 45 (19.8%) were on treatment, 24 (10.6%) have abandoned and 51 (22.5%) had expired. The median duration of follow up was 18 months. The three-year EFS and OS were 71.9% and 74.8% respectively for the entire COHORT, 74.4% and 75.5% for ALL (Acute Lymphocytic Leukemia), 38.4% and 46.1% for AML (Acute Myeloid Leukemia) and 74.3% and 76.6% for solid tumours. Among solid tumours, three-year EFS and OS was of renal tumours 86.9% and of neuroblastoma was 77.7%. Conclusions: We achieved outcomes similar to those from well-established Indian single institute studies. The survival of our paediatric cancer patients can be improved with collaborative effort and establishment of new centres in the periphery.